2014
DOI: 10.1128/mbio.01564-14
|View full text |Cite
|
Sign up to set email alerts
|

Phyllosphere Microbiota Composition and Microbial Community Transplantation on Lettuce Plants Grown Indoors

Abstract: The aerial surfaces of plants, or phyllosphere, are microbial habitats important to plant and human health. In order to accurately investigate microbial interactions in the phyllosphere under laboratory conditions, the composition of the phyllosphere microbiota should be representative of the diversity of microorganisms residing on plants in nature. We found that Romaine lettuce grown in the laboratory contained 10- to 100-fold lower numbers of bacteria than age-matched, field-grown lettuce. The bacterial dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 56 publications
7
48
0
Order By: Relevance
“…However, no previous studies have explored whether phyllosphere bacteria have any role in the persistence of HuNoV on plants. In our study, the overall range of bacterial counts obtained on PID 0 (3.5 and 4.5 log 10 CFU/g for lettuce and spinach, respectively) was similar to previously reported ranges of culturable bacteria on plants cultivated under greenhouse conditions (62,63).…”
Section: Discussionsupporting
confidence: 67%
“…However, no previous studies have explored whether phyllosphere bacteria have any role in the persistence of HuNoV on plants. In our study, the overall range of bacterial counts obtained on PID 0 (3.5 and 4.5 log 10 CFU/g for lettuce and spinach, respectively) was similar to previously reported ranges of culturable bacteria on plants cultivated under greenhouse conditions (62,63).…”
Section: Discussionsupporting
confidence: 67%
“…Further studies of air, soil, and water samples should be done to identify possible inoculum sources. It should be mentioned that all of our L. sativa samples were sown in a greenhouse and grown for 2 weeks before planting in the field, but previous studies have shown that L. sativa plants grown indoors have lower total bacterial quantities than those grown in the field and that field microbiota can successfully colonize plants grown indoors (35). This suggests that the greenhouse period did not greatly influence the lettuce microbiota studied.…”
Section: Discussionmentioning
confidence: 95%
“…However, river water cannot be considered a homogeneous inoculum source for different crops at a single farm. Recently, airborne bacteria have been shown to be important in forming initial phyllosphere communities (33)(34)(35). Further studies of air, soil, and water samples should be done to identify possible inoculum sources.…”
Section: Discussionmentioning
confidence: 99%
“…The results of our study suggest that an Alkanindiges-related population may be enriched in soil after amendment with abundant hydrophobic hydrocarbons. Alkanindiges strains have also been isolated from lettuce plants (47) and clinical samples (48). In this study, the Alkanindiges strain observed after diesel amendment was originally present in unpolluted soil with abundant vegetation located in Laguna Verde at the south of Valparaíso, Chile.…”
Section: Fig 2 Effect Of Diesel Pollution and Bioremediation Treatmenmentioning
confidence: 95%